(untitled) (Ex Chordis, 2024)
Vincenzo de Meglio, pianist and composer, was born in Naples on 9 April 1825. Many of his works were published by Casa Ricordi, confirming that he enjoyed a certain popularity at the time. Vincenzo de Meglio, whose catalogue includes more than 260 titles, often included translations for violin, cello and piano of operas among his works. Transcriptions, elaborations and fantasias for violin, with or without piano accompaniment, often with a strong virtuosic connotation, are part of this editorial strand. The Trio on Giuseppe Verdi’s Opera ‘Rigoletto’, for piano, violin and cello, op. 144, was published by G. Ricordi & C. The cover bears the dedication ‘All’Egregio Artista Ferdinando Pinto’. The occasion for the composition is not known, but from reports in the periodical ‘Napoli Musicale’ the composition would date back to 1872. The Trio is, to all intents and purposes, a fantasy on famous themes: the choice and presentation of the same themes is not placed in the order in which they are presented in the original score, but in a panel elaboration.